The Relationship between Current Patterns and the Distribution of Surface Waste in the Waters of the City of Palopo - Veranika, Veranika; Mahmudin, Mahmudin; Polapa, Funty Septiyawati (Journal of Coastal and Ocean Sciences, 2023)
Marine debris is a solid material that is disposed of or left in the marine environment by the public either intentionally or unintentionally. The purpose of this study is to identify the abundance and weight of waste (mega and macro) and explain the relationship between current patterns and the distribution of surface waste in the waters of Palopo City. The research was conducted in May-July 2023. Sampling data was collected using Neuston nets installed on both sides of the boat. The results showed that the marine debris found in the waters of Palopo City during high and low tide was dominated by plastic waste. The abundance of plastic waste at high tide is higher than at low tide. The accumulation of scattered surface marine debris is carried away by currents due to the intensity of wind and tides and strengthened by the location of the waters close to the mainland of Palopo City so that marine debris carried by wind and currents tends to the south